2022
DOI: 10.1039/d1nr06937c
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled cellulose nanofiber–carbon nanotube nanocomposite films with anisotropic conductivity

Abstract: In this study, a nanocellulose-based material showing anisotopic conductivity is introduced. The material has up to 1000 times higher conductivity along dry-line boundary direction than along radial direction. In addition...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Previous studies reported that cellulose nanofibers could effectively tailor the assembled structure of carbon nanotubes, and anisotropic films can be formed from evaporation boundaries. [ 23 ] Algal polysaccharides could also cause liquid crystal phase during the evaporation of graphene dispersions, implying that the arrangement of the nanoparticles changed from isotropic to anisotropic. [ 24 ] Montmorillonite nanosheets (containing Al–OH) also can achieve constrained assembly by bridging hydrogen and ionic bonds with alginate and Ca 2+ ions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that cellulose nanofibers could effectively tailor the assembled structure of carbon nanotubes, and anisotropic films can be formed from evaporation boundaries. [ 23 ] Algal polysaccharides could also cause liquid crystal phase during the evaporation of graphene dispersions, implying that the arrangement of the nanoparticles changed from isotropic to anisotropic. [ 24 ] Montmorillonite nanosheets (containing Al–OH) also can achieve constrained assembly by bridging hydrogen and ionic bonds with alginate and Ca 2+ ions.…”
Section: Introductionmentioning
confidence: 99%
“…46 In a recent report, Skogberg et al obtained self-assembled CNF/CNT nanocomposite films with anisotropic conductivity through the customized orientation of the high energy sonicated-cationic CNFs (hes-c-CNFs). 49 Fig. 4(b) displays the hypothesized structure of nanocellulose/CNT composite films and their simulated electrical properties, which provides a new solution to prepare nanocellulose-based films with substantial anisotropic conductivity.…”
Section: Nanocellulose and Nanocellulose-based Composite Materialsmentioning
confidence: 99%
“…[5][6][7] To overcome the problem of low thermal conductivity by a matrix, the most common methods tend to add high thermal conductive fillers. Currently, the high thermal conductive fillers that have been studied mainly include carbon fillers (such as graphene, [8][9][10] carbon fiber, 11 and carbon nanotubes 12 ), and ceramic fillers (such as alumina, 13 aluminum nitrite, 14,15 boron nitrite, [16][17][18][19] and silicon carbide [20][21][22] ). Polymer-based thermal conductive composites are commonly prepared using only the hot pressing method, 23,24 in which the two-dimensional (2D) thermal conductive fillers orientate parallel to the horizontal direction of the composite film and then cause poor thermal conductivity in the vertical direction.…”
Section: Introductionmentioning
confidence: 99%